Positive Emotions in Volunteerism - Vecina Jiménez, María Luisa; Chacón Fuertes, Fernando (The Spanish Journal of Psychology, 2005)
Volunteerism is a well consolidated social phenomenon in our society. However, its rapad growth in the last few years has complicated the integration of theoretical knowledge and its application in organizational settings. Taking into account that nowadays, one of the chief problems of volunteer organizations is sustained volunteer service, the object of this work is to verify, within the context of the psychosocial model of sustained volunteerism (Vecina, 2001), the type of relation between the experience of positive emotions in volunteers and their intention of remaining in the organization. This work was carried out on a sample of volunteers who had been in service for less than one year prior to this study.